2014
DOI: 10.1186/s12884-014-0411-1
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate provision of anti-D prophylaxis to RhD negative pregnant women: a scoping review

Abstract: BackgroundThe purpose of this scoping review was to review the literature on healthcare provider provision of anti-D prophylaxis to RhD negative pregnant women in appropriate clinical situations in various healthcare settings.MethodsA scoping review framework was used to structure the process. The following databases were searched: CINAHL (EBSCO), EBM Reviews (OvidSP), Embase (OvidSP), Medline (OvidSP), and Web of Science (ISI). In addition, hand searching of article references was conducted. The search yielde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 29 publications
0
32
0
Order By: Relevance
“…To inform other parameter estimates for this simulation, we conducted an additional literature search to identify relevant systematic reviews of antenatal anti-D prophylaxis. Four relevant reviews [61][62][63][64] were identified. These reviews provided data on the probability estimates of the events used in the simulation study, including sensitisation and compliance rates.…”
Section: Simulation Study Of Clinical Effectivenessmentioning
confidence: 99%
“…To inform other parameter estimates for this simulation, we conducted an additional literature search to identify relevant systematic reviews of antenatal anti-D prophylaxis. Four relevant reviews [61][62][63][64] were identified. These reviews provided data on the probability estimates of the events used in the simulation study, including sensitisation and compliance rates.…”
Section: Simulation Study Of Clinical Effectivenessmentioning
confidence: 99%
“…Any event that can cause a FMH is considered a sensitizing event. These clinical significant clinical events can lead to the potential development of D antibodies in an RhD negative pregnancy (Fyfe et al, 2014). The list of sensitizing events is substantial:…”
Section: History and Discoverymentioning
confidence: 99%
“…Even with the availability of RhIG, RhD negative women are still developing D-antibodies in pregnancy. Fyfe et al (2014), found that in various healthcare settings opportunities for RhD alloimmunization exist because of mismanagement of care; for example, the prophylaxis is not given and/or not given at the right time when a sensitizing event occurs. Absent from the literature are the reasons behind the occurrence risks of this patient safety incident.…”
Section: Current Clinical Managementmentioning
confidence: 99%
See 2 more Smart Citations